Addition of Five New Species to the Orchid Flora of Bhutan IV - Gyeltshen, Phub (2026)
Five orchid species belonging to four genera, namely, Bulbophyllum deergongense, Bulbophyllum nepalense, Liparis sootenzanensis, Spiranthes himalayensis and Zeuxine gracilis, are reported for the first time from Bhutan. These findings are based on systematic native floristic diversity field surveys carried out between 2023 and 2025. We provide descriptions, along with information on type, distribution, phenology, habitat, notes, and colour plates to facilitate accurate species identification and support practical conservation efforts.